Presence of Heavy Metals and Phosphorus in Soils in a Greenhouse Conditions of the Dominican Republic - Núñez-Ramos, Pedro Antonio; Almonte, Isidro; Pérez, Aridio; Avilés-Quezada, Elpidio; López-Rodríguez, Glenny; Martínez, César; Ruíz-Najera, Ramiro Eleazar (REVISTA TERRA LATINOAMERICANA, 2024)
Intensive soil tillage and the development of crops with excessive use of agrochemicals could produce an increase in the content of some heavy metals such as chromium, nickel, cadmium and lead. The determination of these elements under greenhouse conditions has not been properly evaluated in the Dominican Republic. Therefore, the objective of this study was to determine the concentrations of these metals in soils dedicated to horticultural production under greenhouse conditions. The 40 soils from greenhouses in five locations were evaluated: Jarabacoa, Constanza, Moca, Villa Trina and San José de Ocoa. Data were analyzed using descriptive statistics, Pearson evaluation analysis, nonparametric analysis of variance, and Kruskal Wallis test. The average values of Cr, Ni, Cd, and Pb ranged from 27.0 to 63.7, 30.0 to 77.8, < 0.002 to 1.8, and < 0.002 to 29.4 mg kg-1, respectively. The highest average contents of Cr, Ni, Cd and Pb were found in greenhouses in San José de Ocoa with 63.7, 77.8, 1.8 and 29.4 mg kg-1, respectively. The Cd contents in the remaining localities were < 0.002. The Mn and Zn do not present significant statistical dif ferences between locations (P ≤ 0.05); however, Zn is within desirable levels (3-15 mg kg-1). The variation in these concentrations could be attributed to the type of soil and source material, although these factors were not studied. It is concluded that the average contents of the heavy metals evaluated did not exceed the environmental limits. The concentrations are high in some greenhouses, which should draw attention to the possible accumulation of these in the soil and consequently in the crops.